Lipolysis of Burkholderia lata LBBIO-BL02 lipase in simulated human digestive environments: A candidate for enzyme replacement therapy - Oliveira, Bruno Henrique de [UNESP]; Bourlieu, Claire; Lecomte, Jérôme; Villeneuve, Pierre; Nascimento, Valéria M.G.do [UNESP] (Elsevier, 2024)
Lipases, crucial enzymatic tools for potential replacement therapy, must possess specific characteristics for ideal functionality. An effective lipase replacement therapy necessitates the maintenance of robust lipolytic activity at both acidic and neutral pH levels, as well as in the presence of normal and low physiological concentrations of intra-intestinal bile salts. Additionally, it should resist proteolytic digestion by pepsin and trypsin, actively hydrolyzing a wide range of dietary triacylglycerols. This study focuses on the production, purification and biochemical characterization of Burkholderia lata LBBIO-BL02 lipase, emphasizing its potential in digestive environments. The enzyme demonstrated activity against fatty acids with carbon chains from 8 to 20, displaying a preference for palmitic (16:0) and oleic (18:1) acids. It displayed regioselectivity for the external positions sn-1 and sn-3 of triacylglycerol. Kinetic revealed Michaelis-Menten behavior, with a Km of 22 mmol and Vmax of 12.7 mmol/min, with kcat 225s−1 and catalytic efficiency 104 mol−1 s−1. Operating optimally at 55 °C, the enzyme showed stability at 60 °C. The optimal pH range was 4–9, retaining >100% of initial activity in the pH range 2.2–10.0. In simulated gastric environments, the lipase exhibited high activity and stability under low pH conditions, demonstrating remarkable activation in the presence of high bile salt concentrations. BLL emerged as an enzyme comparable in potency to gastric and pancreatic lipases, encompassing a substrate variety while resisting proteases and bile salts. The biochemical insights from this study lay a robust foundation for further exploration of BLL in enzyme replacement therapy.
Keywords: Dietary triacylglycerols; Enzyme replacement therapy; Exocrine pancreatic insufficiency; Pancreatic lipase; Regioselectivity